2017
DOI: 10.1503/cjs.000317
|View full text |Cite
|
Sign up to set email alerts
|

Users’ guide to the surgical literature: how to assess a noninferiority trial

Abstract: DISCUSSIONS IN SURGERY • DISCUSSIONS EN CHIRURGIEUsers' guide to the surgical literature: how to assess a noninferiority trial A well-planned randomized controlled trial (RCT) is the most optimal study design to determine if a novel surgical intervention is any different than a prevailing one. Traditionally, when we want to show that a new surgical intervention is superior to a standard one, we analyze data from an RCT to see if the null hypothesis of "no difference" can be rejected (i.e., the 2 surgical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Twenty-nine trials (n = 3960) 13 14 15 16 17 18 19 21 22 23 24 25 26 28 34 35 36 37 41 42 44 46 47 48 49 52 54 55 56 reported cut out data. Of those trials, 5 reported no event during the course of study (6–40 months) 17 26 30 38 57 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine trials (n = 3960) 13 14 15 16 17 18 19 21 22 23 24 25 26 28 34 35 36 37 41 42 44 46 47 48 49 52 54 55 56 reported cut out data. Of those trials, 5 reported no event during the course of study (6–40 months) 17 26 30 38 57 .…”
Section: Resultsmentioning
confidence: 99%
“…The items included random sequence generation, allocation concealment, blinding of participants, surgeons or outcome assessors, completeness of outcome data, and selective reporting. We included two additional items regarding “standardization of the operative procedures” and “surgeons’ experience clearly defined with operations” because the validity of findings from surgical RCTs depends largely on quality of operation and surgeons’ experience 16 .…”
Section: Methodsmentioning
confidence: 99%
“…It has identified the need to better develop the hiring process so as to make the process more efficient and more likely to yield a satisfactory match for both sides. 22…”
Section: Time Since Trainingmentioning
confidence: 99%
“…As this survey was intended to inform us about current resident satisfaction, a specific sample size was not targeted; instead all residents were surveyed. A cover letter was provided including survey objectives, 26 rationale for respondent selection, 26 department stationary, 27 assurance of confidentiality, 27 estimated time required, 28 and survey deadline. 29 Responses were anonymous.…”
Section: Survey Administrationmentioning
confidence: 99%